RAJA, KARAWITAN, DAN UPACARA TRADISI KERATON SURAKARTA - Joko Daryanto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
Karawitan (gamelan music and singing accompanied by a gamelan) is an integral part of court activities. The very large role of karawitan makes the court karawitan an integral part of court traditional life. The large role of court karawitan is closely related to the traditional ceremonies. The importance of karawitan in the court traditional life finally makes the karawitan one of power legitimacy tools to confirm the king’s power and authority. Thus, there is a unity between the court tradition and karawitan, in other words, karawitan cannot be apart from the court tradition. In other words there is reciprocal and mutual relation between the king, karawitan and court tradition. Such relationship between king, karawitan and court tradition is called system. It is named system because there is a strong reciprocal relationship and the loss of one such element will harm the court traditional life survival.Keywords : king, karawitan, court tradition, system